The Use Of Flat Structure Puzzles To Improve Fine Motor Ability In Students With Visual Disabilities - Nur Rizqi, Ony; Hasan Tino, Ahmad; Khoirin Nada, Anita; Lail Sufiana, Shoumul; Chorynia Ruby, Arcivid (CV RIFAINSTITUT, 2023)
This study aims to determine the process of learning mathematics in students with visual disabilities. Researchers use the experimental method, where the experimental method is part of the quantitative method. Data collection uses a questionnaire to find out the results of learning mathematics in students with visual disabilities. The subject of this study was one of the 3rd-grade students at special education school SDLB Purwosari Kudus who has special needs and is visually impaired. The results of the study show that in the process of teaching activities, the teacher only provides material and the teacher does not provide examples of learning media to students. Students with visual disabilities have difficulties in mathematics lessons, where the teacher only explains the material to students in the process of teaching and learning activities, but students have a high curiosity and enthusiasm for the material being taught. Meanwhile, the limitations of learning media and school facilities are inhibiting factors in teaching and learning mathematics for students with visual disabilities. Seeing these conditions, the researcher chose the Flat Puzzle learning media.